The effectiveness of substance abuse treatment: development of a brief questionnaire (Archives of Clinical Psychiatry, 2015)
Background Practitioners need brief instruments to monitor outcomes in both treatment of drugs and alcohol addiction because they are useful to guide decision making in a short time.Objectives This study aims to develop a brief questionnaire, based on Client Evaluation of Self and Treatment, to evaluate the treatment effectiveness in drug and alcohol addiction treatment settings.Methods A cross-sectional study using a convenience sample (N = 608) recruited from Division for Intervention on Addictive Behaviours and Dependencies (DICAD – ARS North).Results The results show a new four-factor solution that accounted for 54.4% of the total variance and that provides the best fit to the data (c2/df = 1.72, CFI = .94, GFI = .91, RMSEA = .048 [.040-.057]; prmsea = .623). It also revealed a high internal consistency (a = .82). It was found a significant negative correlation (r = - .52, p < .01) between the final version of the instrument and a self report measure of psychopathology symptoms.Discussion This brief questionnaire, with good psychometric properties, can be useful to provide a viable and rapid feedback of treatment outcomes. Further studies should be performed to continue the evaluation of the reliability of this measure.